A novel sensitive electrochemical method for the detection of ractopamine in meat food via polycitrulline-modified electrode. Issue 9 (1st September 2020) - Ma, Xinying; Lv, Huiping; Zhu, Qi; Chen, Meifeng; Wang, Yilei; Li, Fenghai
ABSTRACT: In this paper we report the modification with citrulline of the surface of a glassy carbon electrode (GCE) through cyclic voltammetry to prepare a polycitrulline-modified electrode (PCit/GCE). The electrochemical behaviour of ractopamine on this PCit/GCE was then investigated by cyclic voltammetry, to establish a novel electrochemical method for the detection of ractopamine residues in animal tissue. The optimum preparation conditions for the modified electrode were found to include a polymerisation solution pH of 6.8. The cyclic voltammetry required 12 scan cycles at a scan rate of 40 mV/s with a potential range of −1.6 to 2.3 V. The optimum conditions to determine ractopamine were in a solution of pH 6.0 with cyclic voltammetry performed at a scan rate of 60 mV/s and a potential range of 0.4 to 1.0 V. To analyse meat, the tissue sample was extracted with ethanol, filtered, evaporated to dryness and diluted with phosphate buffered saline at pH of 6.0 before being analysed in the electrochemical cell. The limit of detection of the new method for ractopamine was 1.0 ng/g and the correlation coefficient (R) was 0.9991 in the concentration range of 140–5410 ng/g. Ractopamine residue levels in spiked beef and mutton samples were detected by the modified electrode and the recovery was in the range of 96%-101%, giving results consistent with a validated HPLC method. This study provides a new method for detection and quantification of ractopamine residues in animal tissue. Graphical Abstract: uf0001